The efficiency of Profort additive in feeding cows during the period of increasing the milk yield - A. V. Filatov; N. A. Shemuranova; A. F. Sapozhnikov (Аграрная наука Евро-Северо-Востока, 2019)
The article provides data on the use of Profort feed probiotic additive containing strains of Enterococcus faecium and Bacillus subtilis bacteria in feeding cows during the period of increasing the milk yield. The research was conducted in 2019 on the basis of Agricultural Production Cooperative Collective farm "Iskra", Kirov region. Two groups of highly productive black-and-white motley cows with the average milk yield of 7500 kg for a lactation of 20 animals each were formed for the experiment. The morphological composition and immuno-biochemical parameters of blood of the experimental animals as well as milk productivity and quality indicators of milk were studied, the economic efficiency of Profort probiotic additive use was calculated. It has been established that the inclusion of Profort additive into the animal diet at a dose of 30 g per head per day during 80 days of the period of increasing the milk yield contributes to the normalization of metabolic processes in their bodies, increasing the average daily milk yield by 9.04 – 12.86% (P<0.05), an increase in the percentage of fat and protein in milk by 0.03-0.10%, respectively, compared with the similar indicators of animals in the control group. When using Profort, from the cows of the experimental group in the first three months of lactation 72785.08 kg of milk in a basic fat content of 3.4% were ob-tained, that was 10580.37 kg of milk more as compared with the milk yield of animals from the control group for the same period (62204.71 kg). It allowed to increase the revenue from the sale of milk by 17.01%, to reduce the cost of production of 1 kg of milk by 2 rubles or 11.76% and to get 6.04 rubles of additional profit for each ruble of additional costs. The increase in profit and reduction in the cost of milk production contributed to an increase in profitability by 18.01%.